A preliminary report on the phyllosphere mycoflora of tea and the soil mycoflora of an experimental tea plantation area of Cachar - and BK DUTTA, P.R. DEB, M. DEB* (Indian Phytopathology, 2002)
Observations were made of the tea soil and leaf surface mycoflora of 12 varieties of tea grown in Assam, India. The highest phyllosphere fungi population was found in TV30 and the lowest was found in TV26. Aspergillus, Penicillium and Fusarium werethe predominant species on all of the varieties. The dominant soil fungi were Aspergillus, Penicillium, Fusarium and Cephalosporium.